From England to France : Felony and Exile in the High Middle Ages - Jordan, William Chester, 1948- (Book collections on Project MUSE., 2017)
At the height of the Middle Ages, a peculiar system of perpetual exile- or abjuration-flourished in western Europe. It was a judicial form of exile, not political or religious, and it was meted out to felons for crimes deserving of severe corporal punishment or death. This work explores the lives of these men and women who were condemned to abjure the English realm, and draws on their unique experiences to shed light on a medieval legal tradition until now very poorly understood.